Secession - the Last Resort for Minority Protection - de Villiers, Bertus (Sage Publications, 2013)
'Secession' is a word that brings fear to nations. It reeks of conflict, violence and instability. It is also a measure of last resort. It sometimes brings hope to minorities that are in despair and who feel permanently excluded from policy making. This article looks at some of the faces of secession. It investigates how international law is vague on the one hand and pragmatic on the other hand when it comes to secession. It shows how, in recent times, secession has been endorsed by the international community in cases such as East Timor, Eritrea and Kosovo while in Ethiopia and Canada legal mechanisms exist for managing demands for secession. Consideration is given to some of the pre-requisites for secession. Finally general observations are made about secession as a mechanism to protect minorities.